2009
DOI: 10.1016/j.jcin.2009.04.007
|View full text |Cite
|
Sign up to set email alerts
|

A Prospective, Multicenter, Randomized Trial to Assess Efficacy of Pioglitazone on In-Stent Neointimal Suppression in Type 2 Diabetes

Abstract: Pioglitazone treatment might suppress in-stent neointimal proliferation and reduce incidence of TLR after PCI in patients with T2DM.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
40
1
2

Year Published

2010
2010
2018
2018

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 59 publications
(45 citation statements)
references
References 52 publications
1
40
1
2
Order By: Relevance
“…receiving gliclazide/glimepiride. 262 Thiazolidinediones might be associated with lower restenosis rates after PCI with BMS, 263 but carry an increased risk of heart failure due to fluid retention. No trial has demonstrated that insulin or glucose-insulinpotassium (GIK) improves PCI outcome after STEMI.…”
Section: C -mentioning
confidence: 99%
“…receiving gliclazide/glimepiride. 262 Thiazolidinediones might be associated with lower restenosis rates after PCI with BMS, 263 but carry an increased risk of heart failure due to fluid retention. No trial has demonstrated that insulin or glucose-insulinpotassium (GIK) improves PCI outcome after STEMI.…”
Section: C -mentioning
confidence: 99%
“…Several studies performed in patients with diabetes have demonstrated a reduced incidence of ISR and TLR after BMS deployment associated with peroxisome proliferator-activated receptor agonist administration (96 -98). Accordingly, a recent study showed a lower ISR rate in patients with diabetes treated with DES when pioglitazone was added to standard treatment (96).…”
Section: Therapeutic Implicationsmentioning
confidence: 99%
“…Ponadto zaburzenia rytmu serca i powikłania niedokrwienne występowały rzadziej u pacjentów przyjmujących gliklazyd lub glimepiryd [370]. Stosowanie pochodnych tiazolidynodionu może się wiązać z niższym odsetkiem restenoz po PCI z wszczepieniem BMS [371], jednak niesie ze sobą zwiększone ryzyko niewydolności serca z powodu retencji płynu w nerkach (patrz również część 6.2.6).…”
Section: Rewaskularyzacja Mięśnia Sercowego a Leczenie Hipoglikemizująceunclassified